2013
DOI: 10.1002/pen.23458
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the crystalline structure of polypropylene parts molded through water‐assisted injection molding: Effects of melt temperature and polymeric nucleating agent

Abstract: The melt temperature and a special polymeric nucleating agent [acrylonitrile–styrene copolymer (SAN)] were investigated to find an effective way for tailoring the crystalline structures of the water‐assisted injection‐molded polypropylene (WAIM PP) parts. The results showed that lowering the melt temperature led to the formation of a small amount of β‐form crystals in both outer and core layers of the WAIM PP parts. Nevertheless, the melt temperature had little effect on tailoring the crystalline structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…[140]. It was recently found that shear flow, induced by a special water-assisted injection molding technique [195], can greatly enhance the dispersion and orientation of nanofillers, resulting in interfacial crystallization of the matrix [193]. This contributed largely to the increased thermal stability of the nanocomposite.…”
Section: Polypropylene/clay Nanocomposites -A New Class Of Organic/inmentioning
confidence: 99%
“…[140]. It was recently found that shear flow, induced by a special water-assisted injection molding technique [195], can greatly enhance the dispersion and orientation of nanofillers, resulting in interfacial crystallization of the matrix [193]. This contributed largely to the increased thermal stability of the nanocomposite.…”
Section: Polypropylene/clay Nanocomposites -A New Class Of Organic/inmentioning
confidence: 99%